The Chinese position on the Syrian crisis 2011 - Mushtaq Mal Allah Qasim (Genius Journals, 2022)
The onset of the Syrian crisis coincided with a change in American focus from the Middle East to the Pacific Ocean, creating a regional void that drove some regional governments to fill it. It also provided Russia with an opportunity to return to the scene of political developments in the Middle East. This tendency is congruent with the goal of China, which views American tendencies a direct danger to its security As a result, China is attempting to play a significant international role commensurate with its expanding economic and military might. As a result, Syria has become the pivot of Chinese strategy, as well as the country's nearly exclusive means of attaining its objectives in the area. Based on that foundation, China's viewpoint on the Syrian problem is established in light of America's engagement in Syria. The role highlights China's interactions with the area, as well as the appraisal of its performance within the context of international balances and alliances, making the Chinese visible
Keywords: China; Syria; crisis; position